Siembra de soluciones: Tomo 1. Alternativas políticas en materia de recursos genéticos (actualización de Gente, Plantas y Patentes) - International Development Research Centre; International Plant Genetic Resources Institute; Dag Hammarskjöld Foundation; Crucible II Group (2001)
This is the Spanish translation of Seeding Solutions volume 1. Policy options for genetic resources: People, Plants and Patents revisited The Crucible II Group